Yacón and Scorzonera as functional enrichment of food - Bashta (Sheremet), Alla; Ivchuk, Nadiya; Bashta, Oleksandr (My University, 2015)
The aim of this work was to determine the polysaccharides composition such non-traditional plant materials as Salsify and Yacón and enrichment of food with selected raw materials.
Keywords: polysaccharide; scorzonera; yacón; inulin; health; полісахарид; скорцонера; якон; інулін; здоров’я; кафедра технології оздоровчих продуктів